Searches for 25 rare and forbidden decays of D+ and D+s mesons; Journal of High Energy Physics; Vol. 2021, iss. 6 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2021, 2021)
Title screen